Topology optimization of dji f450 drone arm using finite element analysis and additive manufacturing - A. Andreas; M.A. Choiron; I.M.G. Karohika; A. Ghurri (Dinamika Teknik Mesin, 2026)
This study presents the design, topology optimization, additive manufacturing, and experimental validation of a DJI F450 drone arm to enhance structural efficiency and energy performance. The original arm, made of PA66-30GF, was replaced with PLA for 3D printing, and topology optimization was applied to reduce mass while maintaining stiffness. Static structural simulations under thrust and lateral loads showed that the optimized design (Design 2.0) significantly reduced maximum stress and deformation under vertical load, while remaining within safe limits under lateral load. Experimental deformation tests validated the simulation results, with deviations of 0.64–3.89%. Flight tests demonstrated that Design 2.0 reduced battery consumption by 14.3% during 5-minute hovering, extending flight time by approximately 50 seconds. The study confirms that combining topology optimization with additive manufacturing can produce lightweight, high-performance drone components that improve both structural integrity and operational efficiency.